Optimal energy-efficient shade screen and ventilation control settings for a greenhouse covered with light-altering films - Chavan, Sachin Gorakshnath; Samaranayake, Premaratne; Lan, Yi-Chen; Maier, Chelsea; Liang, Weiguang; Cazzonelli, Christopher I.; Chen, Zhong-Hua; Tissue, David T. (Frontiers in Energy Research, 2025)
IntroductionEnergy management in protected cropping is imperative to sustainably produce food. Optimal energy consumption in a protected cropping facility strongly depends on infrastructure control settings and meteorological conditions. This study aimed to optimise glasshouse energy management by investigating energy consumption under different shading, light-altering and ventilation conditions.MethodsWe compared energy consumption used in heating and cooling under two light-altering films and four different ventilation and shade screen positions. The light-altering glasshouse films, namely, light shifting film (LSF) - Luminescent Light Emitting Agriculture Film (LLEAF), and light blocking film (LBF) - low emissivity film ULR 80 (ultra-low reflectivity with 80% light transmission) were compared to a light diffusing hazed glass as the control.ResultsThe mean combined energy consumption was significantly higher in summer compared to winter. The light treatment and ventilation/shade screen position combinations influenced total heating and cooling energy consumption mostly in summer. The LBF achieved the most efficient total energy consumption, particularly when ventilation was open and shade screens closed during winter, and when both ventilation and shade screens were closed during summer.DiscussionRegardless of the season, cooling energy use was more dependent on the rooftop rather than the outside air temperature, indicating that incoming radiation is the major contributor to glasshouse warming during winter. Therefore, the minimization of energy consumption in protected cropping requires combined management of ventilation settings and light-altering methods to match the seasonal photoperiod and outside temperature environment.